Inventory of Estuarine and Lagoonal Ecosystems Subjected to Sand-Mining Activities in Southern Benin (West Africa) - LALEYE, PHILIPPE A. (My University, 2019)
Sand is a useful resource for the development of any society. As such, the issues related to its extraction are everywhere present in Benin, especially in the southern part of the country. For the purposes of eventually characterizing those issues, the present study is undertaken with a focus on inventorying estuarine and lagoonal ecosystems which are subjected to sand mining in southern Benin. The study area covers both the Eastern Complex and the Western Complex. The Eastern Complex includes the Porto-Novo Lagoon and the Ouémé River delta; while the Western Complex includes the Coastal Lagoon, the Aheme Lake along with its channels, and the Mono Basin. The method used in this study is a systematic inventorying of all known and documented sites as kept on record with relevant state offices in charge of the management of those resources. Then, the data were completed by combing the whole area for direct census observations and field interviews with stakeholders. All inventoried sites have been geo-referenced using a GARMIN GPS and their surface areas have been established. To date, 43 sand-mining sites have been identified, of which 29 are located in the Oueme Delta and in the Porto-Novo Lagoon, 8 are in the Coastal Lagoon, and 6 are in the Aheme Lake and its channels as well as in the Mono River basin. The areas are small in the Oueme Delta, where extraction is mostly manual, but get to be more than 89-ha wide in other places such as the Coastal Lagoon where the process is rather mechanized.
Keywords: Inventory; Sand-Dredging; Aquatic Ecosystems; Southern Benin